A combined anterior cruciate ligament/Meniscal injury alters the patellofemoral joint kinematics of anterior cruciate ligament-deficient knees during a single-leg lunge exercise: A cross-sectional study - Huang, Wenhan; Zeng, Xiaolong; Li, Mengyuan; Chen, Haobin; Lai, Huahao; Yan, Yuan; Zhong, Hua; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Anterior cruciate ligament deficiency (ACLD) is often accompanied by concomitant meniscal tears. The study aimed to assess the kinematic alterations of patellofemoral joint (PFJ) in anterior cruciate ligament deficiency knees with or without meniscal tears during a single-leg lunge. Sixty unilateral anterior cruciate ligament deficiency patients were recruited for the study, including 15 isolated anterior cruciate ligament deficiency patients (group 1), 15 anterior cruciate ligament deficiency patients with medial meniscal tears (group 2), 15 patients with lateral meniscal tears (group 3) and 15 patients with combined medial/lateral meniscal tears (group 4). The patellofemoral joint kinematics were determined by a single fluoroscopic image system. Patellofemoral joint kinematics of contralateral anterior cruciate ligament-intact (ACLI) and anterior cruciate ligament deficiency knees were compared. With or without meniscal tears, anterior cruciate ligament deficiency knees had significantly smaller patellar flexion than the anterior cruciate ligament-intact knees (∼5°–10°; p < 0.05). anterior cruciate ligament deficiency knees had more patellar lateral tilting by approximately 1°–2° than the anterior cruciate ligament-intact knees (p < 0.05) in groups 2, 3, and 4. anterior cruciate ligament deficiency groups with medial meniscal deficiencies showed consistent increased lateral patellar translations (2–4 mm) compared to the anterior cruciate ligament-intact group during a single-leg lunge. The results indicate that meniscal tears alter anterior cruciate ligament deficiency patients’ patellofemoral joint kinematics and the types of the meniscal injuries also affect the patellofemoral joint kinematics. Considering the varying effects of meniscal tears on the patellofemoral joint kinematics, specific treatments for anterior cruciate ligament deficiency patients with meniscal tears should be proposed in some closed kinetic chain (CKC) exercise programs, such as single-leg lunge.